Changes in COPD-related anxiety symptoms during pulmonary rehabilitation: a prospective quantitative and qualitative study - Farver-Vestergaard, Ingeborg; Buksted, Eva Holmegaard; Sørensen, Dorthe; Jonstrup, Sune; Hansen, Henrik; Christiansen, Camilla Fischer; Løkke, Anders (Frontiers in Rehabilitation Sciences, 2024)
BackgroundFear-avoidance in COPD can have detrimental effects on pulmonary rehabilitation (PR) outcomes and is therefore important to address. This prospective study examined changes in and management of COPD-related anxiety symptoms over the course of a PR program.MethodsPatients with COPD referred to 9-weeks of PR in the municipality of Vejle, Denmark from January to December 2022 completed a six-minute walk test (6MWT) and the following questionnaires, both before and after PR: COPD Anxiety Questionnaire 20-item version (CAF-R), measuring COPD-related anxiety; COPD Assessment Test (CAT), measuring COPD-related disability; 12-Item Short-Form Health Survey (SF-12), measuring health-related quality of life (HR-QoL); sociodemographic and disease-related information. After PR, a subsample of the patients took part in semi-structured interviews exploring their understanding of how they managed COPD-related anxiety during PR. Pre- and post-assessment of COPD-related anxiety and other PR outcomes were analysed with t-tests and correlation analyses. Qualitative interviews were analysed using a thematic analysis approach.ResultsA total of 72 patients with COPD (mean ± SD age 71 ± 8, 53% female) were included in the study, and 13 took part in qualitative interviews. A significant decrease in COPD-related anxiety was observed from before to after PR, corresponding to a small effect size (Cohen's d = 0.32; p = 0.018). Reductions in COPD-related anxiety were not associated with improvements in COPD-related disability, HR-QOL, or functional exercise capacity. The qualitative findings identified four anxiety management strategies, i.e., “planning”, “problem-solving”, “accepting”, and “confronting”, which were influenced by interactions with healthcare professionals and co-patients as well as patients’ own perception.ConclusionsCOPD-related anxiety symptoms was reduced after PR, potentially through the use of various management strategies. The strategies appeared to be influenced by interactional factors during the PR program.